2012
DOI: 10.1080/09585192.2011.561221
|View full text |Cite
|
Sign up to set email alerts
|

HR managers and environmental sustainability: strategic leaders or passive observers?

Abstract: INTRODUCTIONWhile many organisations have been quick to jump onboard the 'sustainability bandwagon' little appears to have been done to consider the role of, and effect on, the HR function and manager. In fact, organisations have tended to treat sustainability and HR in silo. This paper examines questions such as: How are HR managers defining and enacting corporate sustainability? And what is the effect of the HR managers' social and political contexts in this role? We do so b y focusing on the relationships b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 46 publications
4
48
0
1
Order By: Relevance
“…In overall, this trend improves the environmental orientation of the organization. This finding parallel to past research works, which found that environmental attitude of employee, has a significant role in environmental orientation of organization (Harris &Tregidga, 2012;Young et al, 2015).…”
Section: Discussionsupporting
confidence: 80%
“…In overall, this trend improves the environmental orientation of the organization. This finding parallel to past research works, which found that environmental attitude of employee, has a significant role in environmental orientation of organization (Harris &Tregidga, 2012;Young et al, 2015).…”
Section: Discussionsupporting
confidence: 80%
“…Overall, the studies in this quadrant adopt relatively narrow definitions of CSR and CS, grounded in the stream of sustainability research that associates CS with environmental dimensions (Starik & Rands, 1995). Consistently with this definition of CSR/CS, environmental sustainability (Harris & Tregidga, 2012;Jackson & Seo, 2010) is the most developed area of studies of HR contributions to CSR/sustainability. The amount of research in this domain reflects the evolutionary pattern of practitioners and scholars' interests, who traditionally, and disproportionately, focused on the environmental dimension of sustainability (Pfeffer, 2010).…”
Section: Internal/process Orientation: Hr For Csrmentioning
confidence: 99%
“…The extent to which HRM is able or effective at yielding such leverage is variable; however, the potential is there to exert influence upward and downward in the organization (Buckley et al, ). Since much of the research emphasis focuses on the power of HRM to secure strategic influence, issues of ethics have not featured strongly in the HRM research agenda (Harris & Tregidga, ).…”
Section: Leadership Integrity and The Role Of Hrmmentioning
confidence: 99%